Alteribacter keqinensis sp. nov., a moderately halophilic bacterium isolated from a soda lake. Issue 5 (3rd May 2022) - Liu, Jiading; Zhang, Xinyu; Cao, Hao; Guo, Liwei; Zhao, Baisuo; Zhang, Xiaoxia; Wang, Yanan; Wang, Haisheng
Abstract : A Gram-stain-positive, aerobic, endospore-forming and rod-shaped bacterium (KQ-3 T ), which grew at 10–45 °C (optimum 35 °C), pH 8.0–10.5 (optimum pH 9.0) and in the presence of 0–16 % (w/v) NaCl (optimum 3.0 %), was isolated from a soda lake and identified as representing a novel species using a polyphasic taxonomic approach. Strain KQ-3 T was catalase-positive, oxidase-negative and non-motile. Phylogenetic analysis based on 16S rRNA gene sequence affiliated KQ-3 T to the genus Alteribacter and showed the highest similarities to Alteribacter natronophilus M30 T (97.90 %), Alteribacter aurantiacus K1-5 T (97.84 %) and Alteribacter populi FJAT-45347 T (97.22 %). Digital DNA–DNA hybridization and average nucleotide identity analyses revealed that KQ-3 T displayed 21.4 and 72.81% genomic DNA relatedness with the most closely related strain, A. natronophilus M30 T, respectively. KQ-3 T contained all of the conserved signature indels that are specific for members of the genus Alteribacter . The DNA G+C content was 45.03 mol%. The cell-wall peptidoglycan contained meso -diaminopimelic acid and the polar lipids consisted of phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol and one unidentified phospholipid. The predominant menaquinone was MK-7 (100%) and the major fatty acids (>10 %) comprised anteiso-C15 : 0, iso-C15 : 0 and iso-C16 : 0 . Based on the data from the current polyphasic studies, KQ-3 T represents a novel species of the genus Alteribacter, for which the name Alteribacter keqinensis sp. nov. is proposed. The type strain is KQ-3 T (=ACCC 61799 T =KCTC 33933 T ).